Komunikasi dan Penyiaran Islam (Pesan Komunikasi Dakwah dalam Keluarga Pada Chanel Youtube Islam itu Indah Official Ustaz Maulana) - Muhammad Sholehuddin Al Qadri; Muktarruddin (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2026)
This study aims to analyze family communication messages of da’wah in the Islam Itu Indah program delivered by Ustaz Maulana on the Islam Itu Indah Official YouTube channel. The research employs qualitative content analysis with a phenomenological approach to understand the meaning, context, and experiences embedded in da’wah messages. Data in the form of sermon videos were analyzed descriptively following Huberman’s model: data reduction, data display, and conclusion drawing. The study focuses on three main themes: the concept of “the highest throne at home”, “mami papi gen z is on fire”, and “husbands should not be stingy to wives”. Findings reveal that da’wah messages do not emphasize hierarchical or dominant family relationships, but rather present a husband-wife partnership built on cooperation, deliberation, and shared responsibility. The effectiveness of message delivery is influenced by the preacher’s interactive communication style, spontaneous humor, strong nonverbal expressions, and the use of popular language relatable to the audience’s daily life. The findings confirm that da’wah through television and social media serves a dual function: conveying religious norms while acting as adaptive education responsive to the dynamics of modern family life, thereby strengthening awareness of the family as a harmonious spiritual partnership space.